An Environmental Impact Analysis of Semi-Mechanical Extraction Process of Sago Starch: Life Cycle Assessment (LCA) Perspective. (May 2018) - Yusuf, M A; Romli, M; Suprihatin,; Wiloso, E I
Abstract: Industrial activities use material, energy and water resources and generate greenhouse gas (GHG). Currently, various regulations require industry to measure and quantify the emissions generated from its process activity. LCA is a method that can be used to analyze and report the environmental impact of an activity that uses resources and generates waste by an industrial activity. In this work, LCA is used to determine the environmental impact of a semi-mechanical extraction process of sago industry. The data was collected through the sago industry in Cimahpar, Bogor. The extraction of sago starch consists of stem cutting, rasping, mixing, filtration, starch sedimentation, washing, and drying. The scope of LCA study covers the harvesting of sago stem, transportation to extraction site, and the starch extraction process. With the assumption that the average transportation distance of sago stem to extraction site is 200 km, the GHG emission is estimated to be 325 kg CO2 eq / ton of sundried sago starch. This figure is lower than that reported for maize starch (1120 kg CO2 eq), potato starch (2232 kg CO2 eq) and cassava starch (4310 kg CO2 eq). This is most likely due to the uncounted impact from the use of electrical energy on the extraction process, which is currently being conducted. A follow-up study is also underway to formulate several process improvement scenarios to derive the design of sago starch processing that generates the minimum emissions.